Facility Relayout Using Systematic Layout Planning and Blocplan Methods to Minimize Material Handling Distance - Nabila Tsaniatu Yulia; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2022)
. A good facility layout will affect sustaining the smoothness of the production process. initial observation on a current CV. NTY is still not good to apply because it does not take into account the degree of proximity. This can be seen from machine laying as well as workstations that look distanced as well as the flow of intersecting material resulting in backtrackings, such as the blowing department towards the cutting department its material removal distance of 23.2 m and having to go through the packing department and plong department with too much distance and intersect caused the production time to become longer. The methods that production facility layout design uses on the CV. NTY is Systematic Layout Planning and Blocplan methods. This method was chosen because it conforms to the company's characteristics and can minimize the distance between production stations as well as no more intersecting production process flow. This study was conducted to find out and obtain improved material distance efficiency in handling the preliminary layout with the proposed layout. The results of the study show the blocplan method has a total decrease in the displacement distance smaller by 60.73 m with an efficiency increase of 42 % as well as improving the flow of the production process in the initial layout.